New insights into the coevolutionary history of termites and their gut flagellates: Description of Retractinympha glossotermitis gen. nov. sp. nov. (Retractinymphidae fam. nov.) - Radek, Renate; Platt, Katja; Öztas, Deniz; Šobotník, Jan; Sillam-Dussès, David; Hanus, Robert; Brune, Andreas (Frontiers in Ecology and Evolution, 2023)
Lower termites harbor diverse consortia of symbiotic gut flagellates. Despite numerous evidence for co-cladogenesis, the evolutionary history of these associations remains unclear. Here, we present Retractinymphidae fam. nov., a monogeneric lineage of Trichonymphida from Serritermitidae. Although Retractinympha glossotermitis gen. nov. sp. nov. morphologically resembles members of the genus Pseudotrichonympha, phylogenetic analysis identified it as sister group of the Teranymphidae. We compared morphology and ultrastructure of R. glossotermitis to that of Pseudotrichonympha and other Teranymphidae, including the so-far undescribed Pseudotrichonympha solitaria sp. nov. from Termitogeton planus (Rhinotermitidae). Like all Teranymphidae, R. glossotermitis is a large, elongated flagellate with a bilaterally symmetric rostrum, an anterior, flagella-free operculum, and an internal rostral tube. However, it is readily distinguished by the length of its rostral flagella, which never exceeds that of the postrostral flagella, and its retractable anterior end. Inclusion of the hitherto unstudied Stylotermes halumicus (Stylotermitidae) in our survey of trichonymphid flagellates in Neoisoptera confirmed that the combined presence of Heliconympha and Retractinympha and absence of Pseudotrichonympha is unique to Serritermitidae. The close phylogenetic relatedness of Heliconympha in Serritermitidae to the spirotrichosomid flagellates in Stolotermitidae provides strong support for their acquisition by horizontal transmission.